Place of death and phenomenon of going home to die in Chinese adults: A prospective cohort study - Li Weng; Yizhen Hu; Zhijia Sun; Canqing Yu; Yu Guo; Pei Pei; Ling Yang; Yiping Chen; Huaidong Du; Yuanjie Pang; Yan Lu; Junshi Chen; et al. (Elsevier, 2022)
Summary: Background: China is embracing an ageing population without sustainable end-of-life care services. However, changes in place of death and trends of going home to die (GHTD) from the hospital remains unknown. Methods: A total of 42,956 participants from the China Kadoorie Biobank, a large Chinese cohort, who died between 2009 and 2017 was included into analysis. GHTD was defined as death at home within 7 days after discharge from the hospital. A modified Poisson regression was used to investigate temporal trends of the place of death and GHTD, and estimate prevalence ratios (PRs) and 95% confidence intervals (CIs) for the association of GHTD with health insurance (HI) schemes. Findings: From 2009 to 2017, home remained the most common place of death (71·5%), followed by the hospital (21·6%). The proportion of GHTD for Urban and Rural Residents' Basic Medical Insurance (URRBMI) beneficiaries was around six times higher than that for Urban Employee Basic Medical Insurance (UEBMI) beneficiaries (66·0% vs 11·6%). Besides, a substantial increase in the proportion of GHTD throughout the study period was observed regardless of HI schemes (4·4% annually for URRBMI, and 5·4% for UEBMI). Compared with UEBMI beneficiaries, URRBMI beneficiaries were more likely to experience GHTD, with an adjusted PR (95% CI) of 1·19 (95% CI: 1·12, 1·27) (P<0·001). Interpretation: In China, most of deaths occurred at home, with a large proportion of decedents GHTD from the hospital, especially for URRBMI beneficiaries. Substantial variation in the phenomenon of GHTD across HI schemes indicates inequalities in end-of-life care utilization. Funding: The National Natural Science Foundation of China, the Kadoorie Charitable Foundation, the National Key R&D Program of China, the Chinese Ministry of Science and Technology.